STUDY OF MOLECULAR INTERACTIONS OF NH -MCM-41 IN PRESENCE OF NICOTINAMIDE (A HYDROTROPIC AGENT) IN ETHANOL FOR PARTIALLY SOLUBLE DRUGS 2 - Swagatika, Srabani; Kumar Dash, Suresh; Dash, Upendra Nath (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACTA solution of NH2-MCM-41 (5 and 10 weight %) has been prepared by taking tetraethylorthosilicate as silica source and 3-amino propyltriethoxysilaneas amine source. The samples were characterized by scanning electron microscopy, X-ray diffraction, and Fourier transform infrared. The density,viscosity, and conductance of NH-MCM-41 (5 and 10 weight %) have been measured in the concentration range of 40-140 ppm in ethanolic solutionof hydrotropic agent nicotinamide at different temperatures ranging from 298.15 to 313.15 K at an interval of 5 K. The density and viscosity datahave been analyzed for the evaluation of limiting apparent molar volume (V2Ï†0), limiting apparent expansibility (E), Falken-Hagen coefficient (a), andJones-Dole coefficient (b). The conductance data have been analyzed by Shedlovsky method to obtain limiting molar conductance (Î›Ï†0) and associationconstant (KA). The thermodynamic parameters such as change in enthalpy (Î”H0), entropy (Î”S0), free energy (Î”G00), and Walden product (Î›) for theion pair formation have been calculated from the value of ion association constant at constant temperature. The results have been discussed in termsof solute-solute; solute-solvent interactions. This investigation would give information regarding pharmacokinetics and pharmacodynamics of thesedrug carriers.Keywords: NH2-MCM-41, Ethanol, Apparent molar volume, Nicotinamide, Association constant.m0Î·0